Hubungan Faktor Fisik, Penyakit Komorbid, dan Faktor Psikis Terhadap Kualitas Hidup Lansia dengan Osteoartritis - Rasyidin, Nur Laelatul; Julianti, Hari Peni; Ngestiningsih, Dwi; Purwoko, Yosef (Medica Hospitalia : Journal of Clinical Medicine, 2021)
ABSTRACT BACKGROUND: Osteoarthritis were the fourth cause of disability in the world in 2020. Limitation of physical activity that occurred in elderly with osteoarthritis can affect the socio-economic aspects of the elderly, causing a decrease in health-related quality of life (HRQoL). In addition to osteoarthritis, recent studies have shown an association between history of hypertension, diabetes, and family support on quality of life in the elderly. OBJECTIVE: To analyze the relationship between physical factors, comorbid diseases, and psychological factors on the quality of life of the elderly with knee osteoarthritis. METHOD: This study was an observational analytic study with a cross-sectional design. The samples were patients with knee OA who underwent therapy at the William Booth Hospital Semarang and the Diponegoro National Hospital that met the inclusion criteria. The research subjects were 61 respondents selected through consecutive sampling. The analysis test performed using the Chi-square method and logistic regression with p-value considered significant if p <0.05. The instrument used in this study was a demographic characteristic questionnaire, VAS, family APGAR, and OPQOL-35. RESULTS: There was a significant relationship in the assessment of the level of pain and family function on the quality of life of the elderly with knee OA (p = 0.003 and p = 0.042). Assessment of other physical factors consisting of gender (p = 0.637), duration of illness (p = 0.2), and degree of radiology (p = 0.532), as well as comorbid factors consisting of hypertension (p = 0.37) and diabetes (p = 0.663), showed an insignificant relationship to the quality of life of the elderly with knee OA. The dominant factor that affected the quality of life of the elderly with knee OA is the level of pain (p = 0.022) with OR value 14.1. CONCLUSION: Factors that affected the quality of life of the elderly with knee OA were the level of pain and family function. Key: knee OA, Quality of Life, Elderly